2015
DOI: 10.1002/alr.21627
|View full text |Cite
|
Sign up to set email alerts
|

Management of cerebrospinal fluid rhinorrhea: an evidence‐based review with recommendations

Abstract: Despite relatively low levels of evidence, recommendations for the management of CSF rhinorrhea can be made based on the current literature. Higher-level studies are needed to better determine optimal clinical management approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 85 publications
(155 reference statements)
2
70
0
6
Order By: Relevance
“…16 Multiple studies have investigated the use of lumbar drains in endoscopic repairs of CSF leak; some concluded that they do not appear to affect the repair rates, 5 or could not ascertain their benefits, 6 and others found that they do not significantly contribute to the success of surgical repairs. 17,18 Most studies in this field included patients with different eitiologies predisposing them to CSF leaks. In a study by Albu et al in which lumbar drains and their effects on recurrence were assessed.…”
mentioning
confidence: 99%
“…16 Multiple studies have investigated the use of lumbar drains in endoscopic repairs of CSF leak; some concluded that they do not appear to affect the repair rates, 5 or could not ascertain their benefits, 6 and others found that they do not significantly contribute to the success of surgical repairs. 17,18 Most studies in this field included patients with different eitiologies predisposing them to CSF leaks. In a study by Albu et al in which lumbar drains and their effects on recurrence were assessed.…”
mentioning
confidence: 99%
“…To date, according to the systematic review by Oakley et al in 2015, there is no aggregate evidence level which can be generated from the available literature to review many adjunctive historic conservative measures. 27 In 2001, a survey of otolaryngologists managing CSF leaks from skull base trauma reported that two-thirds were using lumbar drains routinely. 28 In 2012, Psaltis et al could not ascertain from their meta-analysis the number of cases using lumbar drains, their indications, or their effectiveness.…”
Section: Conservative Managementmentioning
confidence: 99%
“…It can occur following skull base trauma, endoscopic sinus surgery, or neurosurgical procedures, or have a spontaneous etiology [1]. The most common symptom of CSF leak is rhinorrhea.…”
Section: Introductionmentioning
confidence: 99%